The Executive Regulation of the Capital Market law = اللائحة التنفيذية لقانون سوق رأس المال (2025)
1. Issue of Securities -- 2. Stock Exchanges -- 3. Companies Operating in the Field of Stocks and Shares -- 4. Union of Shareholder Workers -- 5. Arbitration and Settlement of Disputes -- 6. Provision Regulating the Securities Portfolios Formation and Management Companies and the Stock brokerage companies -- 7. Dealing in bonds and bond brockerage and agency.